2001
DOI: 10.1039/b104321h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of diphenylmethane from formalin and benzene in a biphasic system with 12-tungstophosphoric acid

Abstract: Heteropoly acids such as H3PW12O40 are exceptionally active catalysts in the synthesis of diphenylmethane from benzene and formalin (aqueous formaldehyde) in a biphasic system and can be recycled simply by drying the aqueous phase at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This easy recovery of catalyst makes this biphasic reaction an environmentally friendly process. 31 The high activity of H 3 PMo 12 O 40 in the reactions performed in biphasic systems was previously reported by us, when we have investigated reactions of H 3 PMo 12 O 40 -catalyzed oxidative desulfurization in a biphasic system CH 3 CN/isooctane. 32 On that system, we carried out the oxidation of thiophene to sulfoxide with hydrogen peroxide and veried that though in the absence of phase transfer catalyst, the H 3 PMo 12 O 40 and its salt AlPMo 12 O 40 were much more active than tungsten heteropolyacids.…”
Section: Assessing the Acidity Strength Of Catalystssupporting
confidence: 53%
“…This easy recovery of catalyst makes this biphasic reaction an environmentally friendly process. 31 The high activity of H 3 PMo 12 O 40 in the reactions performed in biphasic systems was previously reported by us, when we have investigated reactions of H 3 PMo 12 O 40 -catalyzed oxidative desulfurization in a biphasic system CH 3 CN/isooctane. 32 On that system, we carried out the oxidation of thiophene to sulfoxide with hydrogen peroxide and veried that though in the absence of phase transfer catalyst, the H 3 PMo 12 O 40 and its salt AlPMo 12 O 40 were much more active than tungsten heteropolyacids.…”
Section: Assessing the Acidity Strength Of Catalystssupporting
confidence: 53%
“…As shown in Table , conversion of formaldehyde was >93% for H 3 PW 12 O 40 and Sc(CF 3 SO 3 ) 3 . It should be emphasized that only H 3 PW 12 O 40 afforded PhCH 2 Ph (in 35.3% yield, under these conditions).…”
Section: Biphasic System Consisting Of Aqueous Phasementioning
confidence: 76%
“…Furthermore, the direct use of formalin is economical, the byproduct is ideally only water, and the catalyst can be recycled by simple drying of the aqueous phase at room temperature. 66 As shown in Table 9, conversion of formaldehyde was >93% for H 3 PW 12 O 40 and Sc(CF 3 SO 3 ) 3 . 66 It should be emphasized that only H 3 PW 12 O 40 afforded PhCH 2 Ph (in 35.3% yield, under these conditions).…”
Section: Biphasic System Consisting Of Aqueous Phasementioning
confidence: 87%
See 1 more Smart Citation
“…Anderson et al, demonstrated the potential of H 3 PW 12 O 40 (HPW)/MCM-41 catalyst for the acid catalyzed conversion of 1, 3, 5 triisopropyl benzene and found that 23 wt.% loading of the active component was the optimum value [27]. HPW exhibited exceptionally high activity for the synthesis of diphenyl methane compared to conventional mineral acids [28]. Izumi et al, demonstrated the highly active and selective nature of the heteropoly acids for the acetolysis of cyclic ethers (furan, THF, 2-methyl furan, 1, 4 dioxane) compared to either H 2 SO 4 or p-toluene sulphonic acid [29].…”
Section: Introductionmentioning
confidence: 97%